What instruments should we use to assess paediatric decision-making interventions? A narrative review. (September 2020) - Robertson, Eden G; Cohen, Jennifer; Signorelli, Christina; Grant, David M; Fardell, Joanna E; Wakefield, Claire E
There is an increasing number of shared decision-making (SDM) interventions in paediatrics. However, there is little consensus as to the best instruments to assess the feasibility and impact of these interventions. This narrative review aims to answer: (1) what feasibility, knowledge and decision-making instruments have been used to assess paediatric SDM interventions and (2) what are the psychometric properties of used decision-making instruments, guided by the 'consensus-based standards for the selection of health measurement instrument' criteria. We conducted a review of the peer-reviewed literature. We identified 23 studies that evaluated a paediatric intervention to facilitate SDM for a specific health decision. Eighteen studies assessed intervention feasibility, with a wide variability in assessment between studies. Twelve studies assessed objective knowledge, and four studies assessed subjective knowledge with all but one study aggregating correct responses. We identified nine decision-making instruments that had been assessed psychometrically, although few had been thoroughly evaluated. The Decisional Conflict Scale was the most commonly-used instrument and the only instrument evaluated in paediatrics. Our study revealed a lack of consistency in the instruments used to evaluate decision-making interventions in paediatrics, making it difficult to compare interventions. We provide several recommendations for researchers to improve the assessment of SDM interventions in paediatrics.